Tecnologias alternativas de drenagem urbana aplicáveis às cidades de pequeno porte - Bassani, José Henrique (2013)
The drainage systems are essential in urban infrastructure, but its poor performance produces flooding, economic losses, environmental and even loss of life. The small towns for lack of technical and financial structure, often neglect to build strong infrastructures and the use of technologies with environmental sustainability. The growth of cities produces the densification of already urbanized area and moves around it, increasing the impermeability of the soil in the watersheds of the geographical area where it is located. The constructive elements of stormwater drainage in the areas of consolidated urbanization in general are old and have already sizing that do not meet the growing urbanization. The high intervention costs for the replacement or expansion of the dimensional elements of urban drainage infrastructure by traditional processes unfeasible these technologies, considered outdated by their impacts and environmental consequences. The technologies considered alternatives for stormwater drainage systems seek to reduce impacts on the water cycle in urban areas, serving as an important complement to traditional systems, especially in small towns in process of rapid population growth, where the application of these solutions may produce its effects before the frequent occurrence of critical states of flooding. The paper presents possible solutions to applicability in small towns, with proposed methodology and case study in the town of Tapejara, State of Rio Grande do Sul, Brazil. Theresults demonstrate that the non-traditional technologies in urban drainage are advisable and necessary, and serve to revitalize the use of the infrastructure already built, reducing costs and mitigating anthropogenic interventions of urban environments.